Assessment Of Reversibility Of Airway Obstruction In Bronchial Asthma With Pulmonary Function Tests. - CHAUDRY, N T; KHAN, S J; KHAN, T A (Annals of King Edward Medical University, 2020)
Pulmonary function tests (PFTs) are a useful tool in diagnosis of respiratory disorders, assessment of their severity and response to therapy. The evaluation of PFT was conducted in mild asthmatics. The differential evaluation was based on the use of salbutamol as a bronchodilator for 20 cotrol and 20 mild asthmatic subjects in the study group both age and se matched. The baseline value of FEV1, below 80% of predicted standard was used as an index for subclinical hyper responsive behaviour of asthmatic group. Reversibility was defined as a response in FEV1, of 15% or more from baseline or a minimum increase of 200ml after bronchodilator inhalation. Spirometric as well as volume related parameters were measured. Blood gas analysis was also performed. The response of asthmatic group was compared with control group before and after salbutamol inhalation. In mild asthmatic group, statistically highly significant difference (p<0.01) in pre and post bronchodilator values of vital capacity (VC), forced vital capacity (FVC), forced expiratory volume in one second (FEV1, forced expiratory flow 25-75% (FEF 25-75), thoracic gas volume (TGV), airway resistance (Raw) and peak expiratory flow rate (PEFR) shows a decreased hyper responsive behaviour. There was highly significant difference (p<0.01) in base line values of VC, FVC, FEV1, FEV1/FVC %, FEF 25-75%, TGV, Raw and PEFR amongst asthmatic and control groups. This study reveals that flow rates and static lung volumes are helpful in assessing reversibility in airway obstruction.